The Influence of Emotional Intelligence and Spiritual Intelligence on the Performance of Educators at SMP Negeri 5 Sipirok - Lestario, Febrilian; Siregar, Putri Helena (Journal of Community Research and Service, 2024)
SMP Negeri 5 Sipirok is a secondary educational institution situated in the village of Situmba, Sipirok District, under the South Tapanuli Regency. This study aimed to assess the impact of emotional intelligence and spiritual intelligence on teacher performance at SMP Negeri 5 Sipirok Sipirok. This research is classified as associative research. The research population consisted of all employees at SMP Negeri 5 Sipirok Sipirok. The study has a sample size of 32 respondents. The data gathering methods employed in this study encompassed the use of questionnaires and interviews. The study demonstrated that both emotional intelligence and spiritual intelligence had a partially good and significant impact on teacher performance at SMP Negeri 5 Sipirok Sipirok. The equation Y = -21,542 + 0.302 X1 + 0.199 X2 + e, derived from multiple linear regression analysis, indicates a positive and unidirectional association between the variable X and the variable Y. The Adjusted R Square (R2) value of 62% indicates that the combined influence of emotional intelligence and spiritual intelligence on teacher performance at SMP Negei 5 Sipirok is 62%. The remaining 38% is attributed to other variables not considered in this study model.